ΦCrAss001 represents the most abundant bacteriophage family in the human gut and infects Bacteroides intestinalis - Shkoporov, Andrey N. (Nat Commun, 2018)
CrAssphages are an extensive and ubiquitous family of tailed bacteriophages, predicted to infect bacteria of the order Bacteroidales. Despite being found in ~50% of individuals and representing up to 90% of human gut viromes, members of this viral family have never been isolated in culture and remain understudied. Here, we report the isolation of a CrAssphage (ΦCrAss001) from human faecal material. This bacteriophage infects the human gut symbiont Bacteroides intestinalis, confirming previous in silico predictions of the likely host. DNA sequencing demonstrates that the bacteriophage genome is circular, 102 kb in size, and has unusual structural traits. In addition, electron microscopy confirms that ΦcrAss001 has a podovirus-like morphology. Despite the absence of obvious lysogeny genes, ΦcrAss001 replicates in a way that does not disrupt proliferation of the host bacterium, and is able to maintain itself in continuous host culture during several weeks.